IMPROVING THE UNDERSATNDING OF THE GEOMETRIC SHAPES THROUGH GEOBOARD (CLASSROOM ACTION RESEARCH IN GROUP B TK AL-WAFA, SAWANGAN, KOTA DEPOK, 2017) - Nur Aini Zaida (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2018)
The purpose of this research is to explain the process and the result by using geoboard in improving the form of the children in group B TK Islam Al-Wafa, Sawangan, Depok in 2017. This research method using action research method. The research method used is Kemmis Taggart action research model which consists of: (a) planning, (b) action and observation, and (c) reflection. The instruments used in this research are observation, interview, and documentation. The data scores of children's understanding of geometric shapes were analyzed using quantitative and qualitative approaches. Wake shows the child's understanding of geometric shapes has increased. When the pre-test of understanding of the child to the geometry shapes significantly 56.16% and in the first cycle to 66.33%. Score on the second cycle increased approximately 13.33% and got a score of 79.66%. B TK Islam Al-Wafa, Sawangan, Depok in 2017, (2) the understanding of geometry on the group of children of B TK Islam Al-Wafa, Sawangan, Depok in 2017 increased from pre cycle to first cycle and second cycle.